2015
DOI: 10.1002/jcb.25113
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Anti‐Cancer Agent, 1‐(3,5‐Dimethoxyphenyl)‐4‐[(6‐Fluoro‐2‐Methoxyquinoxalin‐3‐yl)Aminocarbonyl] Piperazine (RX‐5902), Interferes With β‐Catenin Function Through Y593 Phospho‐p68 RNA Helicase

Abstract: 1-(3,5-Dimethoxyphenyl)-4-[(6-fluoro-2-methoxyquinoxalin-3-yl)aminocarbonyl] piperazine (RX-5902) exhibits strong growth inhibition in various human cancer cell lines with IC50 values ranging between 10 and 20 nM. In this study, we demonstrate that p68 RNA helicase is a cellular target of RX-5902 by the drug affinity responsive target stability (DARTS) method, and confirmed the direct binding of (3) H-labeled RX-5902 to Y593 phospho-p68 RNA helicase. We further demonstrated RX-5902 inhibited the β-catenin depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 36 publications
3
37
0
Order By: Relevance
“…In this study, we first observed that the natural monoterpenoid 1,8-cineole, which does not contain hydroxyl moieties, exhibits inhibitory effects against UVB-induced COX-2 expression by directly targeting AhR. DARTS is a method that can be used to identify the molecular targets of small molecules without chemical modification, and has been used to successfully identify the molecular targets of some anti-cancer drugs [ 38 , 39 ] and phytochemicals [ 40 , 41 ] without structural limits. However, DARTS has some limitations including drug binding affinity to its target as a limiting factor, the possibility of modifying protease susceptibility of non-target proteins following drug treatment, and low sensitivity with mass spectrometry [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we first observed that the natural monoterpenoid 1,8-cineole, which does not contain hydroxyl moieties, exhibits inhibitory effects against UVB-induced COX-2 expression by directly targeting AhR. DARTS is a method that can be used to identify the molecular targets of small molecules without chemical modification, and has been used to successfully identify the molecular targets of some anti-cancer drugs [ 38 , 39 ] and phytochemicals [ 40 , 41 ] without structural limits. However, DARTS has some limitations including drug binding affinity to its target as a limiting factor, the possibility of modifying protease susceptibility of non-target proteins following drug treatment, and low sensitivity with mass spectrometry [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, phosphorylated-DDX5 (p-DDX5) could be specifically targeted by anticancer molecule exhibiting strong growth inhibition, such as RX-5902 (Supinoxin), which binds directly to p-DDX5 in cancer cells to inhibit the interaction between p-DDX5 and b-catenin pathway resulting in blocking the b-catenin pathway and its downstream genes (e.g. c-Jun, c-Myc and cyclin D1) [287,319]. RX-5902 induced G2/M arrest and apoptosis in TNBC cells, and had additive effects of anti-tumor in vivo, currently, a phase 2 clinical trial in TNBC is ongoing (https://clinicaltrials.gov/ct2/show/NCT02003092) [320].…”
Section: Ddx5 and Breast Cancermentioning
confidence: 99%
“…Interestingly, as a potential target in cancer therapy, DDX5 can be directly targeted by compounds already tested in humans, such as the antioxidant resveratrol (Taniguchi et al, 2016), the active component of green tea epigallocatechin gallate (ECGC) (Tanaka et al, 2011) or the synthetic drug Supinoxin/RX-5902 (Kost et al, 2015). It is conceivable that oligodendrocytespecific targeting of DDX5 could facilitate Mbp translation in vivo, aiding myelination or remyelination in the context of white matter disease.…”
Section: Converging Roads Towards Mbp Expressionmentioning
confidence: 99%